BRITISH MODEL OF HIGHER EDUCATION FINANCING: LESSONS FOR UKRAINE - G. Kharlamova (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The modern system of higher education constantly emphasizes the lack of state funding to ensure the high competitiveness of educational services. The article refers to the main and largest component of the budget of European universities - public funding, tracking the conditions under which its volume is determined. A comparative study of European experience, in particular the UK experience, allows us to identify possible recommendations for the Ukrainian model of higher education financing.